Raça, classe e gênero na educação CTS: um estudo das produções acadêmicas (2020-2023) - Longo, Natalia Gabriela (Universidade Federal de São Carlos, 2026)
Given the history of oppression and domination experienced by diverse social groups, expressed mainly in the form of racial violence, femicide, and homophobia, among others, it is urgent to promote discussions on issues of race, social class, and gender in various spaces in order to understand how these oppressions are established and perpetuated, with a view to overcoming them. In this context, the school environment is a potential setting for promoting these discussions, given its role in educating people for life in society. One way to promote these discussions in schools is through STS education. Thus, this research aimed to analyze how academic research, expressed in dissertations related to STS education in the field of science teaching, produced between 2020 and 2023, has discussed issues of social class, race, and gender. To this end, we conducted a bibliography study, whose dissertations were collected from the Capes thesis and dissertation catalog. Thirty-two dissertations were analyzed, following the steps of Content Analysis. In the categorization process, three categories were defined a priori: race, social class, and gender, and two categories emerged during the analysis: articulations of race, social class, and gender, and approaches to discussions of social class. The results indicate that issues of social class were discussed mainly from the perspective of criticism of science and technological development aligned with the capitalist order. Issues of race involved discussions related to the exploitation and expropriation of people on the African continent for the production of technologies and the hierarchization of scientific content. Gender issues, on the other hand, sparked discussions about the contributions, participation, and challenges faced by women in scientific careers. We found that discussions of social class express a trend in the studies analyzed, while gender issues are explored in greater depth, and race issues have been under-explored. The approach taken in these discussions in STS education has shown potential for enabling understanding of existing social oppression and inequality, allowing for human emancipation and the pursuit of overcoming social inequalities.
Race, class, and gender in CTS education: a study of academic publications (2020–2023)
Keywords: CTS; Pesquisa bibliográfica; Ensino de ciências; Justiça social; STS; Bibliographic research; Science education; Social justice; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; 4. Educação de Qualidade